Optimizing camera‐trapping protocols for characterizing mesocarnivore communities in south‐western Europe. (12th September 2016) - Ferreras, P.; Díaz‐Ruiz, F.; Alves, P. C.; Monterroso, P.
Abstract: Carnivores are elusive, nocturnal and scarce, hence, their detection is difficult. Camera trapping has become a powerful non‐invasive technique for collecting information on such elusive species. Some of its major applications are species inventories and community monitoring. Some efforts have been recently devoted to standardize protocols for monitoring mammal communities in tropical areas. Nevertheless, there is a lack of standardization across studies for monitoring carnivore communities in temperate areas. We aimed to optimize camera‐trapping protocols for monitoring mesocarnivore communities in Mediterranean areas, minimizing sampling effort to accurately estimate species richness. For this purpose, we assessed the effect of number of cameras, time they remain active, area covered and spatial arrangement on species richness estimates. We used between 50 and 60 camera‐traps combined with generalist scent attractants in two national parks located in central Spain. We generated random sets of 5–40 cameras and evaluated the accumulated richness between 1 and 30 days since deployment. Generalized linear model analysis indicates that active days, number of cameras, covered area and study area best explained species richness. A minimum of 30 active cameras during 20 days were required for attaining the asymptotical species richness. A larger effort was required to detect all species in the study area with higher species richness (six vs. five species). These results agree with the effort required for obtaining at least one camera image of those species with the lowest detection rates. Scattered deployments required less effort (number of cameras) to reach an asymptote of species richness than clumped layouts, although differences were not significant. These findings can be used as guidelines for monitoring mesocarnivore communities with camera‐traps in temperate areas, although particular monitoring requirements will depend on the community composition and density of mesocarnivore species present in a given study area. Abstract : We aimed to optimize camera‐trapping protocols for monitoring mesocarnivore communities in Mediterranean areas. A minimum of 30 active cameras during 20 days were required for attaining the asymptotical species richness. These findings can be used as guidelines for monitoring mesocarnivore communities with camera‐traps in temperate areas.